Synthesis and Characterization of Dicobalt-Iron Complex (μ3-S)FeCo2(CO)8(Ph2PMe) - Gao, Wei (Asian Journal of Chemistry, 2015)
Treatment of the dicobalt-iron complex (μ3-S)FeCo2(CO)9 (1) with a monophosphine ligand Ph2PMe in CH2Cl2 produced the dicobalt-iron complex (μ3-S)FeCo2(CO)8(Ph2PMe) (2) in 41 % yield. The new complex 2 was structurally characterized by IR, 1H NMR, 31P1H NMR and 13C1H NMR spectroscopy.